2016
DOI: 10.1097/md.0000000000002346
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Severely Displaced Radial Neck Fractures in Children With Percutaneous K-wire Leverage and Closed Intramedullary Pinning

Abstract: To evaluate the efficacy and safety of percutaneous K-wire leverage (PKWL) reduction and closed intramedullary pinning (CIMP) for the treatment of pediatric radial neck fractures.From June 2010 to December 2013, a total of 50 children with Judet III and IV radial neck fractures were treated at our hospital. Manual closed reduction was first attempted to reduce the radial neck fractures. Upon successful closed reduction or the radial neck–shaft angle was reduced to <45°, radial intramedullary pinning or CIMP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…In 1980, Métaizeau 16 was the first to report the use of a closed reduction of the intramedullary nail to treat the radial fracture in children, with good postoperative efficacy. For radial fracture with severe displacement and angulation, however, it can be difficult to achieve reduction using the Métaizeau technique alone, 5,7,10 and the use of open reduction has therefore been advocated in these cases. 17…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1980, Métaizeau 16 was the first to report the use of a closed reduction of the intramedullary nail to treat the radial fracture in children, with good postoperative efficacy. For radial fracture with severe displacement and angulation, however, it can be difficult to achieve reduction using the Métaizeau technique alone, 5,7,10 and the use of open reduction has therefore been advocated in these cases. 17…”
Section: Resultsmentioning
confidence: 99%
“…Radial neck fracture is common in children, accounting for approximately 1%–2.7% of all children’s fractures and 5%–10% of elbow fractures. 15 Severely displaced Judet IV radial neck fractures are not easy to treat using minimally invasive methods such as the Métaizeau technique and single Kirschner (k)-wire percutaneous leverage reduction, 2,47 while open reduction may aggravate the elbow injury, increase the risk of radial necrosis and non-union, and decrease treatment effectiveness. 3,8,9 Furthermore, some researchers have suggested that open reduction does not influence the overall treatment effectiveness of radial neck fracture.…”
mentioning
confidence: 99%
“…In 1993, Metaizeau et al reported intramedullary nailing as a surgical option for the treatment of displaced radial neck fractures [4]. The main superiority of intramedullary fixation is that it simultaneously allows for accurate and stable reduction without disturbing the blood supply [20]. However, this treatment must be performed carefully to protect the superficial branch of the radial nerve and the radial physis [21].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, most surgeons agreed that closed reduction might fail in severely displaced fractures [1, 20, 21]. However, few of those authors analyzed why the closed reduction failed and how closed reduction can be achieved for the failed cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that either the acceptable value of radial neck angle after the operation should be under 20° that the reduction was adequate. 2 , 5 , 7 , 21 Any residual tilt more than 20° was related with the poor outcomes, which could affect functional results adversely. In our study, all reductions were anatomically which was supported by excellent results.…”
Section: Discussionmentioning
confidence: 99%